2015
DOI: 10.1155/2015/142586
|View full text |Cite
|
Sign up to set email alerts
|

Atlantoaxial Subluxation due to an Os Odontoideum in an Achondroplastic Adult: Report of a Case and Review of the Literature

Abstract: The authors report the first example of an adult achondroplastic dwarf with progressive quadriparesis secondary to atlantoaxial subluxation as a consequence of an os odontoideum. Actually, craniocervical region is a frequent site of compression and myelopathy in achondroplasia particularly in children as a result of small foramen magnum and hypertrophied opisthion. Moreover, very rarely in achondroplastic patients, coexistence of atlantoaxial instability as the sequel of os odontoideum can result in further co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…5,10 The implication of OO in individuals suffering from Down syndrome and skeletal dysplasia, such as Morquio disease, multiple epiphyseal dysplasia, achondroplasia, pseudoachondroplasia, Larsen syndrome, and chondrodystrophia calcificans congenital are in favour of its congenital etiology. 9,72,78,79 The association between OO and achondroplasia was first reported by Gulati and Rout in 1974, and since then, 5 more children with related symptoms have been reported. 9 However, this coexistence in achondroplastic adults is an extremely rare occurrence and has been reported in the intensive research undertaken by Rahimizadeh et al in 2015.…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…5,10 The implication of OO in individuals suffering from Down syndrome and skeletal dysplasia, such as Morquio disease, multiple epiphyseal dysplasia, achondroplasia, pseudoachondroplasia, Larsen syndrome, and chondrodystrophia calcificans congenital are in favour of its congenital etiology. 9,72,78,79 The association between OO and achondroplasia was first reported by Gulati and Rout in 1974, and since then, 5 more children with related symptoms have been reported. 9 However, this coexistence in achondroplastic adults is an extremely rare occurrence and has been reported in the intensive research undertaken by Rahimizadeh et al in 2015.…”
Section: Introductionmentioning
confidence: 94%
“…9,72,78,79 The association between OO and achondroplasia was first reported by Gulati and Rout in 1974, and since then, 5 more children with related symptoms have been reported. 9 However, this coexistence in achondroplastic adults is an extremely rare occurrence and has been reported in the intensive research undertaken by Rahimizadeh et al in 2015. 9 In 1999, Taggard et al reported the study of 33 patients with Down syndrome who had craniocervical instability.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations